Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fsurg.2022.908909
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Targeted Post-operative Nursing Outcome in 1246 Patients with Percutaneous Transhepatic Biliary Drainage

Abstract: Jaundice is a detection index in many disease conditions commonly characterized by yellowish staining of the skin and mucous membranes. This work studies the postoperative care outcome in 1,246 patients (669 males and 577 females) with obstructive jaundice who underwent percutaneous transhepatic biliary drainage (PTBD). These patients were admitted to the interventional vascular surgery department of our hospital from February 2017 to February 2022. From the results, frequent wound re-dressing and maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…In addition to the national government strengthening the creation of nurse talent teams and the provision of welfare protection from macro policies, medical institutions should also implement reasonable human resource allocation strategies. 32 It is critical that the nurses who provide care to patients have the best medical knowledge, 21 because their nursing behaviour and quality can affect patient outcomes. A national survey in the Netherlands found that nurses working in hospital gastrointestinal surgery had a low overall knowledge of PTBD placement procedures and catheter care, with half of the nurses reporting that their existing knowledge was insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the national government strengthening the creation of nurse talent teams and the provision of welfare protection from macro policies, medical institutions should also implement reasonable human resource allocation strategies. 32 It is critical that the nurses who provide care to patients have the best medical knowledge, 21 because their nursing behaviour and quality can affect patient outcomes. A national survey in the Netherlands found that nurses working in hospital gastrointestinal surgery had a low overall knowledge of PTBD placement procedures and catheter care, with half of the nurses reporting that their existing knowledge was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that healthcare professionals should pay more attention to the psychological state of PTBD patients, which is consistent with the findings of Mo Wei's study 20 . For patients with benign obstructive jaundice, PTBD can facilitate the rapid relief of jaundice and infection symptoms and provide a method for follow‐up treatment 21 . The relatively short time these patients had spent on the tube may have contributed to their positive attitude.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations